Cortico-Hippocampal Computational Modeling Using Quantum-Inspired Neural Networks - Khalid, Mustafa; Wu, Jun; Ali, Taghreed M.; Ameen, Thaair; Altaher, Ali Salem; Moustafa, Ahmed A.; Zhu, Qiuguo; Xiong, Rong (Frontiers in Computational Neuroscience, 2020)
Many current computational models that aim to simulate cortical and hippocampal modules of the brain depend on artificial neural networks. However, such classical or even deep neural networks are very slow, sometimes taking thousands of trials to obtain the final response with a considerable amount of error. The need for a large number of trials at learning and the inaccurate output responses are due to the complexity of the input cue and the biological processes being simulated. This article proposes a computational model for an intact and a lesioned cortico-hippocampal system using quantum-inspired neural networks. This cortico-hippocampal computational quantum-inspired (CHCQI) model simulates cortical and hippocampal modules by using adaptively updated neural networks entangled with quantum circuits. The proposed model is used to simulate various classical conditioning tasks related to biological processes. The output of the simulated tasks yielded the desired responses quickly and efficiently compared with other computational models, including the recently published Green model.